2017
DOI: 10.1007/s11095-017-2123-5
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Promise of Therapeutic Extracellular Vesicles: The Devil is in Details of Therapeutic Loading

Abstract: Extracellular vesicles (EVs) represent a class of cell secreted organelles which naturally contain biomolecular cargo such as miRNA, mRNA and proteins. EVs mediate intercellular communication, enabling the transfer of functional nucleic acids from the cell of origin to the recipient cells. In addition, EVs make an attractive delivery vehicle for therapeutics owing to their increased stability in circulation, biocompatibility, low immunogenicity and toxicity profiles. EVs can also be engineered to display targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 114 publications
(142 reference statements)
0
99
0
Order By: Relevance
“…An exciting aspect of EVs is their potential to be used as a method to deliver therapeutics. Extracellular vesicles are known to travel long distances through the blood stream and to have some specificity for particular tissues, and since they are lipid derived, they also pass through tissues (Ha et al, ; Sutaria et al, ). Particularly exciting is that it is fairly easy to “load” EVs with drugs or proteins of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exciting aspect of EVs is their potential to be used as a method to deliver therapeutics. Extracellular vesicles are known to travel long distances through the blood stream and to have some specificity for particular tissues, and since they are lipid derived, they also pass through tissues (Ha et al, ; Sutaria et al, ). Particularly exciting is that it is fairly easy to “load” EVs with drugs or proteins of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For larger molecules, a variety of methods to create pores in the EVs have been developed. Importantly, once the treatment is removed, the EVs return to their original form (Ha et al, ; Sutaria et al, ). Examples of the use of EVs as a delivery system include the use of curcumin (Ha et al, ), catalase (Haney et al, ), as well as mRNA and miRNA (Ha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that NSC culture‐conditioned media and purified media products inhibit apoptosis, reduce lesion size, and promote functional recovery in stroked preclinical models (Akerblom, Sachdeva, & Jakobsson, ; Delaloy et al, ; Madelaine et al, ; Stappert, Roese‐Koerner, & Brustle, ; Sutaria, Badawi, Phelps, & Schmittgen, ; Webb, Kaiser, Jurgielewicz et al, ; Webb, Kaiser, Scoville et al, ; Yang et al, ; Zhang et al, ). In a recent rat study utilizing NSC culture‐conditioned media directly, they showed a neuroprotective effect on tissue and functional improvement in a 21‐point behavioral test.…”
Section: Neural Stem Cell‐conditioned Mediamentioning
confidence: 99%
“…These effects were attributed to NSCs releasing neurotrophic factors as well as micro‐ and nano‐sized extracellular vesicles (EVs) into the culture media. EVs derived from various cell sources have been shown to carry protein, DNA, and RNA cargoes that have therapeutic properties (Sutaria et al, ; Webb, Kaiser, Jurgielewicz et al, ; Zhang et al, ). Indeed, recent studies by Webb et al demonstrated that EVs derived from NSCs mitigated the systemic immune response, reduced infarct volume, inhibited hemorrhagic transformation, improved white matter integrity, and promoted functional recovery in two divergent preclinical stroke models‐ mouse thromboembolic and pig permanent middle cerebral artery occlusion stroke model (Webb, Kaiser, Jurgielewicz et al, ; Webb, Kaiser, Scoville et al, ).…”
Section: Neural Stem Cell‐conditioned Mediamentioning
confidence: 99%
“…Current methods of loading therapeutic molecules into EVs such as electroporation, genetic engineering of host cells and chemical conjugation, are limited by low efficiency, toxicity and lack of scalability 9,10 . Moreover, they produce a heterogeneous population of EVs that imposes further complexity in understanding the phenotypic effects of EVs in target cells 11,12 . It is important to understand the intracellular pathways of EV biogenesis, so that the natural characteristics of EVs can be exploited for therapeutic applications.…”
mentioning
confidence: 99%